IDENTIFICATION OF FACTORS AFFECTING USER ACCEPTANCE OF THE SURPLUS FOOD ORDERING APPLICATION - Anberty Paro Uli, Mutiara
PT. Ekonomi Sirkular Indonesia (Surplus) developed an application called Surplus – Food Rescue App to buy surplus food from restaurants, hotels, cafes, and others at lower prices. This application has been operating since March 2020, but as of February 2021, only 880 users are actively opening and using this application out of a total of 4,179 installed applications. The result of the preliminary study indicates several issues which tend users to discontinue using the app. This shows that the user acceptance of the Surplus app has not been settled. Therefore, this study aims to identify factors that influence the user acceptance of the Surplus app. This study used a research model from Chotigo & Kadono in 2021 which consists of price value, social influence, habit, trust, convenience, application quality, satisfaction, and intention constructs. Moreover, there was an additional construct of various food choices. This research was conducted by distributing questionnaires containing 30 question indicators to 83 respondents. Data were processed using the partial least square-structural equation modeling (PLS-SEM) using SmartPLS3. Furthermore, importance-performance matrix analysis (IPMA) was conducted to determine the priority of constructs/indicators that should be prioritized to improve user acceptance. The results showed five significant factors that influence the intention of using the Surplus app which are social influence, habit, application quality, satisfaction, and various food choices. Furthermore, the results of the IPMA showed that an indicator from various food choices should be prioritized for improvement. Based on that indicator, four of seven proposed suggestions related to improving the user acceptance of the Surplus app were considered by the company.